Low cost iodine doped graphene for fuel cell electrodes. (26th October 2017) - Marinoiu, Adriana; Gatto, Irene; Raceanu, Mircea; Varlam, Mihai; Moise, Calin; Pantazi, Aida; Jianu, Catalin; Stefanescu, Ioan; Enachescu, Marius
Abstract: In this work, iodine-doped graphene (I-Gr) was successfully prepared using the electrophilic substitution method and was characterized using micro-Raman spectroscopy, X-Ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. I-Gr was integrated into a cathode electrode, as microporous layer. A simple, time-efficient and reliable test protocol was employed for the screening of the new cathode catalyst layers for the PEM fuel cell. A new approach on an aggressive accelerated degradation testing (ADT) protocol along with the monitoring of electrochemical performances response was introduced in order to investigate the degradation. The 400 cycle's operation, totalizing 100 h, was performed for specific sequences of current cycling steps. Electrochemical performances, including polarization curves (I-V), electrochemical surface area (ECSA), and linear sweep voltammetry (LSV) were measured and analyzed every 25 h in order to investigate the performance decreasing trend during the proposed ADT. This reported 100 h test provides very limited information and requires further investigation. Highlights: I-doped graphenes were prepared by electrophilic substitution method. I-doped graphene was integrated into cathode electrode, as microporous layer. Simple efficient protocol ADT was employed in screening new cathode catalyst layer. The 400 cycles operation was performed for sequences of current cycling.